AB0824 Predictors of Cerebrovascular Disease Among Psoriatic Arthritis Patients. (9th June 2015) - Queiro, R.; Acasuso, B.; Morante, I.; Cabezas, I.; Tejόn, P.; Alperi, M.; Arboleya, L.; Riestra, J.L.; Ballina, J.
Abstract : Background: Patients with psoriasis and psoriatic arthritis (PsA) have a higher prevalence of cardiovascular risk factors (CVRF) compared with normal population. Because of this, they also have higher risk of developing coronary heart disease, however the frequency and predictors of cerebrovascular disease have not been sufficiently studied in these populations. Objectives: To analyze the frequency and determinants of cerebrovascular disease in a cohort of patients with PsA. Methods: Retrospective cohort study that included 205 patients with PsA (CASPAR criteria) of a single university institution. Cerebrovascular disease was defined as any transient or permanent event as a result of a disorder of cerebral circulation either ischemic or hemorrhagic diagnosed by a neurologist. The variables included were: age, sex, education level, age at onset of disease, family history, type and severity of psoriasis, HLA-B*27 and C*06, articular pattern, classic CVRF, BMI, and medication. Univariate and multivariate analyses were performed. All patients gave informed consent. An institutional ethics committee approved the final version of this study. Results: Of the 205 patients enrolled, 9 (4.4%) had cerebrovascular disease (6 ischemic stroke, 2 transient and one hemorrhagic stroke). In the univariate analysis, these patients had a low educational level (100% vs. 40.3% p=0.003), pustular psoriasis (33.3% vs. 3.6%, p<0.0001), and erythrodermic (11.1% vs. 2%, p=0.05), polyarthritis as debut (77.8% vs. 36.7%, p=0.013), diabetes (66.7% vs. 9.7%, p<0.0001), hypertension (77.8% vs. 28.6%, p=0.002), dyslipidemia (55.6% vs. 29.6%, p=0.05), ischemic heart disease (44.4% vs. 2.6%, p<0.0001) and peripheral vascular disease (33.3% vs. 1.5%, p<0.0001). In multivariate analysis, the predictors of cerebrovascular disease were: pustular psoriasis (OR 10.9, 95% CI: 1.2-100.2, p=0.034), erythrodermia (OR 31.2, 95% CI: 1.8-540.5, p=0.019), polyarticular onset (OR 7.8, 95% CI: 1.06-57.3, p=0.044), diabetes (OR 9.7, 95% CI: 1.60-58.9, p=0.013) and ischemic heart disease (OR 23, 95% CI: 3.07-172.2). Conclusions: Cerebrovascular disease is common in PsA. Patients with the most severe phenotypes of psoriatic disease are at high risk for developing cerebrovascular disease. Also, patients who are older at PsA onset and those with other CV comorbidities are a high risk group for stroke. Disclosure of Interest: None declared